Dithieno-cyclopentadiene copolymer photovoltaic material, preparation method and photovoltaic application of dithieno-cyclopentadiene copolymer photovoltaic material
By synthesizing dithiophene cyclopentadiene copolymer photovoltaic materials, the challenges of polymer solar cell materials in terms of energy level, band gap, planarity and stability optimization are solved, and efficient photoelectric conversion and high energy conversion efficiency are achieved.
Patent Information
- Application Number
- CN202411909519.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
Existing polymer solar cell materials have challenges in optimizing energy levels, band gaps, planarity and stability, and it is difficult to simultaneously improve open circuit voltage, short circuit current and photoelectric conversion efficiency.
By synthesizing a dithiopheneocyclopentadiene-based copolymer photovoltaic material, dithiopheneocyclopentadiene and benzothiadiazole-based copolymer are connected by Stille coupling method to form an electron donor material with a carbon-carbon single bond connection.
It has achieved high-efficiency photoelectric conversion of polymer solar cell materials, with the highest energy conversion efficiency reaching 5.44%, and has shown good photoelectric conversion characteristics and application prospects.
Smart Images

Figure CN119775539A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer photovoltaic materials, and in particular to dithienocyclopentadiene copolymer photovoltaic materials, preparation methods and photovoltaic applications thereof. Background Art
[0002] With the increasing depletion of fossil energy, finding a clean renewable energy source has become a major issue of great concern to countries around the world. Solar energy is the most ideal alternative energy source for mankind in the future. How to make full use of solar energy has become a key research topic in the scientific community. Solar cells, the core device for converting solar energy into electrical energy, have become a hot topic of research in the scientific community of various countries and a focus of development and promotion in the industry. Polymer solar cells, which have emerged in recent years, have outstanding advantages such as low cost, light weight, simple manufacturing process, and can be prepared into large-area flexible devices. In addition, there are many types of organic materials, and the performance of solar cells can be improved by modifying the structure of the materials. Therefore, polymer solar cells have important scientific research value and industrial application prospects.
[0003] Non-fullerene polymer solar cells have made rapid progress in the past decade, achieving an energy conversion efficiency of more than 19%. However, the performance of polymer donor materials and non-fullerene acceptor materials needs to be optimized, such as: (1) obtaining higher open circuit voltage and short circuit current by regulating the energy level and band gap of polymer materials; (2) improving the planarity of polymer materials to increase their charge mobility, but in this process, the solubility and stability of the materials must be ensured. These factors are interrelated. Ideally, these factors should be optimized simultaneously, but in reality this is very difficult. Therefore, finding a balance point to achieve the maximum photoelectric conversion efficiency of the cell is the key for material chemists to design polymer donor materials. In the process of designing polymer materials for polymer solar cells, the following principles should be followed: (1) the polymer should have a narrow band gap; (2) a high molar extinction coefficient; (3) good planarity; (4) high charge mobility; (5) good photostability. At the same time, higher molecular weight, higher charge mobility, optimized morphology, filling factor, etc. can all affect the performance of the material. Summary of the invention
[0004] The invention synthesizes dithienocyclopentadiene monomers, obtains dithienocyclopentadiene and benzothiadiazole copolymer solar cell materials by Stille coupling method, performs thermal, optical and electrochemical characterization on them, and applies them to solar cells.
[0005] The purpose of the present invention is to propose a dithienocyclopentadiene copolymer photovoltaic material, a preparation method and photovoltaic applications thereof. The polymer photovoltaic material is a dithienocyclopentadiene copolymer photovoltaic material connected by a carbon-carbon single bond and can be used as an electron donor material in solar cells.
[0006] Based on the above purpose, the present invention provides a dithienocyclopentadiene copolymer photovoltaic material, the structure of the polymer photovoltaic material is shown in the formula:
[0007]
[0008] The dithienocyclopentadiene copolymer photovoltaic material provided by the present invention has good processability and has good photoelectric conversion characteristics as shown by preliminary attempts, and has broad application prospects as a working medium for polymer solar cells.
[0009] Furthermore, the present invention also provides a method for preparing the dithienocyclopentadiene copolymer photovoltaic material, comprising the following steps:
[0010] 1) Under argon protection, 2,6-dibromodithienocyclopentadiene and potassium tert-butoxide are mixed in ethanol, stirred for 30 minutes, and then 5-isooctylfuran-2-carboxaldehyde is added at 60° C. After completion, the reaction is continued at 60° C. for 12 hours, cooled to room temperature, poured into water, extracted, dried, the solvent is spin-dried, and passed through a silica gel column to obtain 4-(5-isooctylfuranylmethylene)-2,6-dibromodithienocyclopentadiene;
[0011] 2) Under argon protection, 2,6-dibromodithienocyclopentadiene and potassium tert-butoxide are mixed in ethanol, stirred for 30 minutes, and then 5-isooctylthiophene-2-carboxaldehyde is added at 60° C. After completion, the reaction is continued at 60° C. for 12 hours, cooled to room temperature, poured into water, extracted, dried, the solvent is spin-dried, and passed through a silica gel column to obtain 4-(5-isooctylthiphenylmethylene)-2,6-dibromodithienocyclopentadiene;
[0012] 3) Under argon protection, 2,6-dibromodithienocyclopentadiene and potassium tert-butoxide are mixed in ethanol, stirred for 30 minutes, and then 4-isooctyloxybenzaldehyde is added at 60° C. After completion, the reaction is continued at 60° C. for 12 hours, cooled to room temperature, poured into water, extracted, dried, the solvent is spin-dried, and passed through a silica gel column to obtain 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene;
[0013] 4) under argon protection, 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole and 4-(5-isooctylfurylmethylene)-2,6-dibromodithienocyclopentadiene were added to anhydrous toluene, and then tetrakis(triphenylphosphine)palladium was added, reacted at 115° C. for 24 hours, cooled to room temperature, precipitated, filtered, and extracted with Soxhlet to obtain polymer P1;
[0014] 5) Under argon protection, 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole and 4-(5-isooctylthienylmethylene)-2,6-dibromodithienocyclopentadiene were added to anhydrous toluene, and then tetrakis(triphenylphosphine)palladium was added, and the mixture was reacted at 115° C. for 24 hours, cooled to room temperature, precipitated, filtered, and subjected to Soxhlet extraction to obtain polymer P2;
[0015] 6) Under argon protection, 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole and 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene were added to anhydrous toluene, and then tetrakis(triphenylphosphine)palladium was added, and the mixture was reacted at 115° C. for 24 hours. The mixture was cooled to room temperature, precipitated, filtered, and extracted with Soxhlet to obtain polymer P3.
[0016] The structural formula of 4-(5-isooctylfurylmethylene)-2,6-dibromodithienocyclopentadiene is as shown below (F-DTC):
[0017]
[0018] The structural formula of 4-(5-isooctylthienylmethylene)-2,6-dibromodithienocyclopentadiene is shown below (T-DTC):
[0019]
[0020] The structural formula of 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene is shown below (B-DTC):
[0021]
[0022] The structural formula of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole is as shown below (DTBT):
[0023]
[0024] The synthetic routes of the target polymers (P1, P2, P3) of the present invention are as follows:
[0025]
[0026] In the present invention, preferably, the molar ratio of 2,6-dibromodithienocyclopentadiene to 5-isooctylfuran-2-carbaldehyde in step 1) is 1:1.0-1.5, and the reaction temperature is 55-65°C.
[0027] In the present invention, preferably, the molar ratio of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole to 4-(5-isooctylfurylmethylene)-2,6-dibromodithienocyclopentadiene in step 2) is 1:1, and the reaction temperature is 110-115°C.
[0028] In the present invention, preferably, the molar ratio of 2,6-dibromodithienocyclopentadiene to 5-isooctylthiophene-2-carboxaldehyde in step 3) is 1:1.0-1.5, and the reaction temperature is 55-65°C.
[0029] In the present invention, preferably, the molar ratio of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole to 4-(5-isooctylthienylmethylene)-2,6-dibromodithienocyclopentadiene in step 4) is 1:1, and the reaction temperature is 110-115°C.
[0030] In the present invention, preferably, the molar ratio of 2,6-dibromodithienocyclopentadiene to 4-isooctyloxybenzaldehyde in step 5) is 1:1.0-1.5, and the reaction temperature is 55-65°C.
[0031] In the present invention, preferably, the molar ratio of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole to 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene in step 6) is 1:1, and the reaction temperature is 110-115°C.
[0032] The invention synthesizes a novel dithienocyclopentadiene electron donor unit, and connects the dithienocyclopentadiene unit with another electron acceptor unit dithiophenebenzothiadiazole through a carbon-carbon single bond by a Stille coupling method to obtain a dithienocyclopentadiene copolymer photovoltaic material. The dithienocyclopentadiene copolymer has good solubility in common organic solvents (such as chloroform, toluene, chlorobenzene, tetrahydrofuran, etc.), and can be used to prepare high-quality polymer films by a solution spin coating method. At the same time, the polymer donor photovoltaic materials have complementary optical absorption and matching HOMO and LUMO energy levels with fullerene acceptor materials. A polymer solar cell is prepared using the polymer as an electron donor and an organic small molecule as an electron acceptor, and the maximum energy conversion efficiency thereof can reach 5.44%, with good photoelectric conversion efficiency.
[0033] Therefore, further, the present invention also provides the use of the dithienocyclopentadiene copolymer photovoltaic material in solar cells.
[0034] In the present invention, preferably, the dithienocyclopentadiene copolymer photovoltaic material is used as an electron donor material for solar cells.
[0035] The present invention uses the above-mentioned dithienocyclopentadiene copolymer photovoltaic material as an electron donor material and applies it to polymer solar cells. The preparation method thereof is as follows:
[0036] The dithienocyclopentadiene copolymer electron donor material of the present invention is mixed with an electron acceptor (fullerene) material, chlorobenzene is added to fully dissolve the mixture, and the mixture is spin-coated on a conductive glass ITO to prepare a conductive film, and then a metal aluminum electrode is evaporated on the film.
[0037] The dithienocyclopentadiene copolymer photovoltaic material provided by the invention has complementary optical absorption and matching HOMO and LUMO energy levels with fullerene acceptor materials, and the molecular structure of the synthetic product in each step is characterized by nuclear magnetic resonance spectrum, mass spectrum and elemental analysis. The optical properties of the dithienocyclopentadiene copolymer photovoltaic material are studied by ultraviolet-visible absorption spectrum. The electrochemical properties of the dithienocyclopentadiene copolymer photovoltaic material are studied by cyclic voltammetry. A solar cell device is made by using the dithienocyclopentadiene copolymer as an electron donor, and a good photoelectric conversion efficiency is obtained.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The synthesis route of the present invention is simple, the cost is low, and the synthesis method is universal, and can be well promoted and applied to the synthesis of other dithienocyclopentadiene photovoltaic materials.
[0040] (2) The dithienocyclopentadiene polymer photovoltaic material of the present invention has optical absorption complementary to that of the fullerene acceptor material, which can ensure that enough solar photons are absorbed to obtain a high photocurrent.
[0041] (3) The dithienocyclopentadiene polymer photovoltaic material of the present invention has a relatively planar conjugated structure, which is beneficial to the separation and transmission of carriers, thereby obtaining a higher fill factor.
[0042] (4) The present invention uses dithienocyclopentadiene copolymer photovoltaic materials as electron donor materials and applies them to polymer solar cells to achieve a higher energy conversion efficiency (PCE=5.44%), which has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions in the present disclosure, the following briefly introduces the drawings required to be used in some embodiments of the present disclosure. Obviously, the drawings described below are only drawings of some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can also be obtained based on these drawings. In addition, the drawings described below can be regarded as schematic diagrams, and are not limitations on the actual size of the product involved in the embodiments of the present disclosure, the actual process of the method, the actual timing of the signal, etc.
[0044] Figure 1 This is an absorption spectrum of the dithienocyclopentadiene copolymer photovoltaic material of the present invention;
[0045] Figure 2 This is an electrochemical analysis diagram of the dithienocyclopentadiene copolymer photovoltaic material of the present invention;
[0046] Figure 3 This is a diagram of the photoelectric conversion efficiency of the dithienocyclopentadiene copolymer photovoltaic material of the present invention. DETAILED DESCRIPTION
[0047] In order to enable those skilled in the art to better understand the technical solutions in this application, the following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0048] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0049] The synthesis route of the dithienocyclopentadiene copolymer photovoltaic material of the present invention is as follows:
[0050]
[0051] Example 1
[0052] Preparation of poly{4-(5-isooctylfurylmethylene)dithienocyclopentadiene-5',6'-dioctyloxy-4',7'-dithienylbenzothiadiazole}(P1)
[0053] ①Synthesis of compound F-DTC
[0054] Under argon protection, 2,6-dibromo-4H-cyclopenta[2,1-b:3,4-b']dithiophene (0.672g, 2mmol) and potassium tert-butoxide (0.448g, 4mmol) were mixed in a reaction bottle, and then 15mL of ethanol was added, stirred until completely dissolved, heated to 60°C, stirred for 1h, and 5-isooctylfuran-2-carboxaldehyde (0.609g, 3mmol) (dissolved in 5mL of ethanol before addition) was added. The reaction system immediately turned red. After continuing the reaction for 12h, the heating was stopped and cooled to room temperature to obtain a red viscous liquid. Dissolved in dichloromethane, washed with water, extracted, collected the organic phase, and distilled under reduced pressure to remove excess solvent to obtain a crude product. Passed through a column (the eluent was petroleum ether: dichloromethane = 20:1) to obtain a red viscous compound F-DTC (0.933g, yield: 88.7%).
[0055] The NMR spectrum and mass spectrum of compound F-DTC are shown below:
[0056] 1HNMR (400MHz, CDCl3, ppm): δ = 7.56 (d, 1H), 7.42 (d, 1H), 7.15 (s, 1H), 6.7 3(s,1H),6.25(s,1H),2.80(d,2H),2.01(s,1H),1.35(t,8H),0.89(t,6H).
[0057] GC-MS: m / z = 526.
[0058] ②Synthesis of polymer P1
[0059] Compound F-DTC (52.6 mg, 0.1 mmol) and compound DTBT (88.2 mg, 0.1 mmol) were added to 12 mL of anhydrous toluene and nitrogen was passed for 20 minutes to expel oxygen from the reaction system. Pd(PPh3)4 (15 mg) was then added and reacted at 115°C for 24 hours. The reaction was stopped and cooled to room temperature. The reaction mixture was poured into 200 mL of methanol for precipitation. After filtering through a Soxhlet extractor, it was extracted with methanol and n-hexane in turn until colorless, and then extracted with chloroform as a solvent until colorless. The chloroform solution was collected and dried to obtain a black solid, which was dried overnight under vacuum to obtain polymer P1 (70 mg, yield: 74%).
[0060] The gel permeation chromatography analysis of polymer P1 is shown below:
[0061] Mn=13,400, Mw=31,700, PDI=2.4.
[0062] Example 2
[0063] Preparation of poly{4-(5-isooctylthienylmethylene)dithienocyclopentadiene-5',6'-dioctyloxy-4',7'-dithienylbenzothiadiazole}(P2)
[0064] ①Synthesis of compound T-DTC
[0065] Under argon protection, 2,6-dibromo-4H-cyclopenta[2,1-b:3,4-b']dithiophene (0.672g, 2mmol) and potassium tert-butoxide (0.448g, 4mmol) were mixed in a reaction bottle, and then 15mL of ethanol was added, stirred until completely dissolved, heated to 60°C, stirred for 1h, and 5-isooctylthiophene-2-carboxaldehyde (0.672g, 3mmol) (dissolved in 5mL of ethanol before addition) was added. The reaction system immediately turned red. After continuing the reaction for 12h, the heating was stopped and cooled to room temperature to obtain a red viscous liquid. Dissolved in dichloromethane, washed with water, extracted, collected the organic phase, and distilled under reduced pressure to remove excess solvent to obtain a crude product. Passed through a column (the eluent was petroleum ether: dichloromethane = 20:1) to obtain a red viscous compound T-DTC (1.01g, yield: 93.2%).
[0066] The NMR spectrum and mass spectrum of compound T-DTC are shown below:
[0067] 1HNMR (400MHz, CDCl3, ppm): δ = 7.73 (s, 1H), 7.22 (s, 2H), 7.15 (s, 1H), 6.81 (s, 1H), 2.83 (d, 2H), 1.70 (s, 1H), 1.27 (t, 8H), 0.87 (t, 6H).
[0068] GC-MS: m / z = 542
[0069] ②Synthesis of polymer P2
[0070] Compound T-DTC (54.2 mg, 0.1 mmol) and compound DTBT (88.2 mg, 0.1 mmol) were added to 12 mL of anhydrous toluene and nitrogen was passed for 20 minutes to expel oxygen from the reaction system. Pd(PPh3)4 (15 mg) was then added and reacted at 115°C for 24 hours. The reaction was stopped and cooled to room temperature. The reaction mixture was poured into 200 mL of methanol for precipitation. After filtering through a Soxhlet extractor, it was extracted with methanol and n-hexane in turn until colorless, and then extracted with chloroform as a solvent until colorless. The chloroform solution was collected and dried to obtain a black solid, which was dried overnight under vacuum to obtain polymer P2 (59 mg, yield: 61%).
[0071] The gel permeation chromatography analysis of polymer P2 is shown below:
[0072] Mn=24,900, Mw=39,200, PDI=1.6.
[0073] Example 3
[0074] Preparation of poly{4-(4-isooctyloxyphenylmethylene)dithienocyclopentadiene-5',6'-dioctyloxy-4',7'-dithienylbenzothiadiazole}(P3)
[0075] ①Synthesis of compound B-DTC
[0076] Under argon protection, 2,6-dibromo-4H-cyclopenta[2,1-b:3,4-b']dithiophene (0.672g, 2mmol) and potassium tert-butoxide (0.448g, 4mmol) were mixed in a reaction bottle, and then 15mL of ethanol was added, stirred until completely dissolved, heated to 60°C, stirred for 1h, and 4-isooctyloxybenzaldehyde (0.702g, 3mmol) (dissolved in 5mL of ethanol before addition) was added. The reaction system immediately turned orange. After continuing the reaction for 12h, the heating was stopped and cooled to room temperature to obtain an orange viscous liquid. Dissolved in dichloromethane, washed with water, extracted, collected the organic phase, and distilled under reduced pressure to remove excess solvent to obtain a crude product. Passed through a column (the eluent was petroleum ether: dichloromethane = 20:1) to obtain an orange solid compound B-DTC (0.745g, yield: 67.5%).
[0077] The NMR spectrum and mass spectrum of compound B-DTC are shown below:
[0078] 1HNMR (400MHz, CDCl3, ppm): δ = 7.67 (s, 1H), 7.59 (s, 1H), 7.54 (d, 1H), 7.48 (d, 1H), 7.4 4(d,1H),7.08(d,1H),6.90(d,1H),3.91(d,2H),1.82(s,1H),1.27(t,8H),0.87(t,6H).
[0079] GC-MS: m / z = 552.
[0080] ②Synthesis of polymer P3
[0081] Compound B-DTC (55.2 mg, 0.1 mmol) and compound DTBT (88.2 mg, 0.1 mmol) were added to 12 mL of anhydrous toluene and nitrogen was passed for 20 minutes to expel oxygen from the reaction system. Pd(PPh3)4 (15 mg) was then added and reacted at 115°C for 24 hours. The reaction was stopped and cooled to room temperature. The reaction mixture was poured into 200 mL of methanol for precipitation. After filtering through a Soxhlet extractor, it was extracted with methanol and n-hexane in turn until colorless, and then extracted with chloroform as a solvent until colorless. The chloroform solution was collected and dried to obtain a black solid, which was dried overnight under vacuum to obtain polymer P3 (78 mg, yield: 80%).
[0082] The gel permeation chromatography analysis of polymer PWDTBXF-B-2Cl is shown below:
[0083] Mn=11,600, Mw=21,800, PDI=1.8.
[0084] Example 4
[0085] Preparation of polymer solar cells
[0086] The present invention uses dithienocyclopentadiene copolymers as working media, and the method for preparing solar cells is: mixing the above-mentioned dithienocyclopentadiene copolymer material with an appropriate amount of fullerene electron acceptor, adding an appropriate amount of solvent to dissolve, preparing a layer of translucent film on ITO (indium tin oxide) conductive glass by conventional spin coating, and then preparing a metal electrode on the photovoltaic active layer by vacuum evaporation.
[0087] The specific steps are: 2.0 mg of P1 and 5.0 mg of PC71BM are mixed, 0.35 mL of chlorobenzene is added to dissolve, a layer of about 120 nm thick film is prepared on the conductive glass modified with PEDOT:PSS by spin coating, and then a metal electrode is prepared on the photovoltaic active layer with aluminum / lithium fluoride by vacuum evaporation. The performance of its polymer solar cell device is as follows:
[0088] Short circuit current = 10.94 mA / cm2; open circuit voltage = 0.84 V; fill factor = 56%;
[0089] Energy conversion efficiency under simulated sunlight (AM1.5, 100 mW / cm2) = 5.15%.
[0090] Example 5
[0091] Preparation of polymer solar cells
[0092] 2.0 mg of P2 was mixed with 5.0 mg of PC71BM, and 0.35 mL of chlorobenzene was added to dissolve it. A thin film of about 120 nm thick was prepared on the conductive glass modified with PEDOT:PSS by spin coating, and then a metal electrode was prepared on the photovoltaic active layer with aluminum / lithium fluoride by vacuum evaporation. The performance of the polymer solar cell device is as follows:
[0093] Short circuit current = 11.42 mA / cm2; open circuit voltage = 0.85 V; fill factor = 56%;
[0094] Energy conversion efficiency under simulated sunlight (AM1.5, 100 mW / cm2) = 5.44%.
[0095] Example 6
[0096] Preparation of polymer solar cells
[0097] 2.0 mg of P3 was mixed with 5.0 mg of PC71BM, and 0.35 mL of chlorobenzene was added to dissolve it. A 120 nm thick film was prepared on the PEDOT:PSS modified conductive glass by spin coating, and then a metal electrode was prepared on the photovoltaic active layer with aluminum / lithium fluoride by vacuum evaporation. The performance of the polymer solar cell device is as follows:
[0098] Short circuit current = 10.04 mA / cm2; open circuit voltage = 0.83 V; fill factor = 57%;
[0099] Energy conversion efficiency under simulated sunlight (AM1.5, 100 mW / cm2) = 4.73%.
[0100] Example 7
[0101] Spectral analysis of polymers P1, P2, and P3
[0102] The optical properties of polymers P1, P2 and P3 were tested by UV-visible absorption spectroscopy. Figure 1 As shown, the three polymers have a wide absorption platform in the state of chloroform solution. Polymers P1, P2 and P3 all have two absorption peaks, and their absorption peaks in the long-wave range are at 648, 615 and 585nm respectively; the absorption in the long-wave range is mainly caused by the DA charge transfer on the polymer main chain. In the film state, polymers P1, P2 and P3 show wider absorption compared to their solution state, and there is a certain red shift. This is because the molecular structure of the polymer in the film state has better planarity and stronger electronic interactions between the main chains. Through the absorption sidebands of the polymers in the film, we can deduce that the optical band gaps of polymers P1, P2 and P3 are 1.46, 1.43 and 1.67eV respectively.
[0103] Example 8
[0104] Analysis of electrochemical properties of polymers P1, P2, and P3
[0105] The electrochemical properties of polymers P1, P2 and P3 were studied by cyclic voltammetry. Figure 2 It is the cyclic voltammogram of polymers P1, P2 and P3. Polymers P1, P2 and P3 all show reversible or quasi-reversible oxidation processes. The initial oxidation potentials of polymers P1, P2 and P3 are 1.05V, 1.09 and 1.15V, respectively, and their corresponding HOMO energy levels are -5.85eV, -5.89eV and -5.95eV, respectively. The initial reduction potentials of polymers P1, P2 and P3 are -0.84V, -0.87V and -0.81V, respectively, and their corresponding LUMO energy levels are -3.96eV, -3.93eV and -3.99eV, respectively. It can be seen from the CV curve that the energy level of the copolymer can be regulated by changing the electron acceptor unit. The electrochemical band gaps of polymers P1, P2 and P3 are 1.89eV, 1.96eV and 1.96eV, respectively.
[0106] Example 9
[0107] Photovoltaic performance analysis of polymers P1, P2, and P3
[0108] In order to study the potential application of polymers P1, P2 and P3 in solar cells, we fabricated bulk heterojunction polymer solar cell devices with the device structure of ITO / PEDOT:PSS / P1orP2orP3:PC71BM / LiF / Al. The photovoltaic devices were tested under standard simulated sunlight (AM1.5G, 100mW / cm2). Figure 3 The relationship between the current density and voltage (IV) of the device is shown, and the detailed device results are summarized in Table 1. In order to optimize the device performance, polymers P1, P2 and P3 were blended with PC71BM at different mass ratios (1:1, 1:1.5, 1:2, 1:2.5, 1:3). When polymers P1, P2 and P3 were blended with PC71BM at a mass ratio of 1:2.5, the best power conversion efficiency (PCE) was obtained.
[0109] Among them, the energy conversion efficiency (PCE) reaches 5.44% when P2:PC71BM=1:2.5, the corresponding open circuit voltage (V℃)=0.85V, short circuit current (Jsc)=11.42mA / cm2, and fill factor (FF)=0.56.
[0110] Table 1 Photovoltaic performance results of polymers P1, P2, and P3
[0111]
[0112]
[0113] It can be seen from Examples 1-9 that the synthesis route of the present invention is simple, the cost is low, and the synthesis method is universal, and can be well promoted and applied to the synthesis of other dithienocyclopentadiene materials; the dithienocyclopentadiene polymer photovoltaic material of the present invention has a strong electron donating effect to produce resonant energy transfer, and is expected to obtain a wider ultraviolet-visible absorption spectrum; the dithienocyclopentadiene polymer photovoltaic material of the present invention has a lower HOMO energy level and high stability to oxygen, which is conducive to the preparation of solar cell devices with more stable performance; the present invention uses dithienocyclopentadiene polymer photovoltaic material as an electron donor material, and is applied to polymer solar cells to obtain a higher energy conversion efficiency (PCE=5.44%), which has a good application prospect.
[0114] In summary, the present invention synthesizes a dithienocyclopentadiene polymer electron donor unit, and connects the dithienocyclopentadiene donor unit with another electron acceptor unit dithiophenebenzothiadiazole through a carbon-carbon single bond by a Stille coupling method to obtain a two-dimensional conjugated dithienocyclopentadiene polymer photovoltaic material. They have good solubility in common organic solvents (such as chlorobenzene, dichlorobenzene, toluene, etc.), and can be used to prepare high-quality films by a solution method. At the same time, these polymer photovoltaic materials have wide visible light absorption, suitable HOMO and LUMO energy levels and relatively narrow band gaps. A polymer solar cell is prepared using this type of polymer as an electron donor and fullerene as an electron acceptor, and its maximum energy conversion efficiency can reach 5.44%, with good photoelectric conversion efficiency.
[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
[0116] The above describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claim involved.
[0117] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A dithienocyclopentadiene copolymer photovoltaic material, characterized in that: The structure of the polymer photovoltaic material is shown in the formula:
2. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 1, characterized in that: The following steps are involved: 1) Under argon protection, 2,6-dibromodithienocyclopentadiene and potassium tert-butoxide are mixed in ethanol, stirred for 30 minutes, and then 5-isooctylfuran-2-carboxaldehyde is added at 60° C. After completion, the reaction is continued at 60° C. for 12 hours, cooled to room temperature, poured into water, extracted, dried, the solvent is spin-dried, and passed through a silica gel column to obtain 4-(5-isooctylfuranylmethylene)-2,6-dibromodithienocyclopentadiene; 2) Under argon protection, 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole and 4-(5-isooctylfurylmethylene)-2,6-dibromodithienocyclopentadiene were added to anhydrous toluene, and then tetrakis(triphenylphosphine)palladium was added, and the mixture was reacted at 115° C. for 24 hours, cooled to room temperature, precipitated, filtered, and subjected to Soxhlet extraction to obtain polymer P1; 3) Under argon protection, 2,6-dibromodithienocyclopentadiene and potassium tert-butoxide were mixed in ethanol, stirred for 30 minutes, and then 5-isooctylthiophene-2-carboxaldehyde was added at 60° C. After completion, the reaction was continued at 60° C. for 12 hours, cooled to room temperature, poured into water, extracted, dried, the solvent was spin-dried, and passed through a silica gel column to obtain 4-(5-isooctylthiphenylmethylene)-2,6-dibromodithienocyclopentadiene; 4) under argon protection, 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole and 4-(5-isooctylthienylmethylene)-2,6-dibromodithienocyclopentadiene were added to anhydrous toluene, and then tetrakis(triphenylphosphine)palladium was added, and the mixture was reacted at 115° C. for 24 hours, cooled to room temperature, precipitated, filtered, and subjected to Soxhlet extraction to obtain polymer P2; 5) Under argon protection, 2,6-dibromodithienocyclopentadiene and potassium tert-butoxide are mixed in ethanol, stirred for 30 minutes, and then 4-isooctyloxybenzaldehyde is added at 60° C. After completion, the reaction is continued at 60° C. for 12 hours, cooled to room temperature, poured into water, extracted, dried, the solvent is spin-dried, and passed through a silica gel column to obtain 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene; 6) Under argon protection, 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole and 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene were added to anhydrous toluene, and then tetrakis(triphenylphosphine)palladium was added, and the mixture was reacted at 115° C. for 24 hours. The mixture was cooled to room temperature, precipitated, filtered, and extracted with Soxhlet to obtain polymer P3.
3. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 2, characterized in that: In step 1), the molar ratio of 2,6-dibromodithienocyclopentadiene to 5-isooctylfuran-2-carboxaldehyde is 1:1.0-1.5, and the reaction temperature is 55-65°C.
4. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 2, characterized in that: In step 2), the molar ratio of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole to 4-(5-isooctylfurylmethylene)-2,6-dibromodithienocyclopentadiene is 1:1, and the reaction temperature is 110-115°C.
5. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 2, characterized in that: In step 3), the molar ratio of 2,6-dibromodithienocyclopentadiene to 5-isooctylthiophene-2-carboxaldehyde is 1:1.0-1.5, and the reaction temperature is 55-65°C.
6. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 2, characterized in that: In step 4), the molar ratio of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole to 4-(5-isooctylthienylmethylene)-2,6-dibromodithienocyclopentadiene is 1:1, and the reaction temperature is 110-115°C.
7. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 2, characterized in that: In step 5), the molar ratio of 2,6-dibromodithienocyclopentadiene to 4-isooctyloxybenzaldehyde is 1:1.0-1.5, and the reaction temperature is 55-65°C.
8. The method for preparing the dithienocyclopentadiene copolymer photovoltaic material according to claim 2, characterized in that: In step 6), the molar ratio of 5,6-dioctyloxy-4,7-di(5-trimethyltin-thienyl)-benzothiadiazole to 4-(4-isooctyloxyphenylmethylene)-2,6-dibromodithienocyclopentadiene is 1:1, and the reaction temperature is 110-115°C.
9. Use of the dithienocyclopentadiene copolymer according to claim 1 in solar cells.
10. The use in solar cells according to claim 9, characterized in that: The dithienocyclopentadiene copolymer photovoltaic material is used as an electron donor material for solar cells.
Citation Information
Cited By
Organic photovoltaic polymer donor material, preparation process and application
CN120737316A
Stretchable donor polymer as well as preparation method and application thereof
CN121495089A
A stretchable donor polymer and a preparation method and application thereof
CN121495089B